Culture Internalization at SMP Islam Al-Azhaar Tulungagung in Fostering The Student's Spiritual Quotient - M. Takviana (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2017)
Tenacious culture of pesantren can foster the student’s spirituality. The students’ intelligence is not only in relation with intelligent quotient but also emotional quotient and spiritual quotient that take main roles in comprehensively building the intelligence. Spiritual quotient is a foundation to accelerate between intelligent quotient and spiritual quotient. This research employed qualitative method. The research data were gathered from interviews, observations and documentations. The process of data analysis encompass collecting the data, verifying the data and concluding the data. The result of the research exemplifies that 1) SMP alAzhaar Tulungagung has positive pesantren culture, 2) SMP Islam al-Azhaar Tulungagung insert the pesantren culture into two ways by instilling the pesantren culture accommodated and integrated through school program, 3) condition of spiritual quotient of student has a significant change identified from the attitude and behaviour that are sustainably supervised by teacher committee during the learning and teaching process and the report of parents at home.